2004
DOI: 10.1177/089686080402400302
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Osteodystrophy in Peritoneal Dialysis Patients

Abstract: The term “renal osteodystrophy” encompasses all forms of metabolic bone disease found in dialysis patients. The primary approach to the treatment of renal osteodystrophy in peritoneal dialysis (PD) patients is similar to that in hemodialysis patients. However, the increased prevalence of adynamic bone histology, together with the difficulty in judging calcium balance, the inability to practicably give intravenous vitamin D, and the clearance of vitamin D and parathyroid hormone via dialysate require a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In the published work, there is no agreed definition of recurrence of hyperparathyroidism but it is now known that iPTH values below twice of normal are associated with low-turnover bone disease while those above 7-8 times of normal are associated with high-turnover bone disease. 25,26 So this patient developed adynamic bone disease 17 months after the total parathyroidectomy without autoimplant, followed by a recurrence of the hyperparathyroidism, at least biochemically, 4 years after the operation. MIBI 6 years postparathyroidectomy showed an abnormal area of uptake in the neck.…”
Section: Discussionmentioning
confidence: 93%
“…In the published work, there is no agreed definition of recurrence of hyperparathyroidism but it is now known that iPTH values below twice of normal are associated with low-turnover bone disease while those above 7-8 times of normal are associated with high-turnover bone disease. 25,26 So this patient developed adynamic bone disease 17 months after the total parathyroidectomy without autoimplant, followed by a recurrence of the hyperparathyroidism, at least biochemically, 4 years after the operation. MIBI 6 years postparathyroidectomy showed an abnormal area of uptake in the neck.…”
Section: Discussionmentioning
confidence: 93%
“…Brown tumour (osteitis fibrosa cystica) occurs in <5% of patients with pHPT in developed countries [ 7 ]. It also occurs in secondary and tertiary hyperparathyroidism particularly among dialysis patients, particularly with PTH > 50 pmol/l [ 8 ]. It is a benign, non-neoplastic tumour characterized by subperiosteal bone resorption and osteopenia [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toussaint et al (2006) reviewed dialysate calcium concentration in HD and concluded that while medications are evolving, and new regimes for HD are emerging, flexibility needs to be maintained and dialysate Ca individualised. Moe (2004) concluded that individualisation of dialysate Ca is necessary for the management of renal osteodystrophy in PD patients. It seems likely that at least two dialysate Ca concentrations will be required to optimise bone management in any patient group.…”
Section: Individualising Dialysate Calciummentioning
confidence: 99%